Holy water changes EEG and HRV because of both autosuggestion and his information (God Grace, World Mind, Cosmic Energy etc) - Popovych, I L; Babelyuk, V Ye; Gozhenko, A I; Zukow, W; Zubov, P G; Dubkova, G I; Korolyshyn, T A; Nesterova, L F; Barylyak, L G (Journal of Education, Health and Sport, 2015)
Popovych I L, Babelyuk V Ye, Gozhenko A I, Zukow W, Zubov P G, Dubkova G I, Korolyshyn T A, Nesterova L F, Barylyak L G. Holy water changes EEG and HRV because of both autosuggestion and his information (God Grace, World Mind, Cosmic Energy etc). Journal of Education, Health and Sport. 2015;5(1):203-220. ISSN 2391-8306. DOI: 10.5281/zenodo.14881 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%281%29%3A203-220 https://pbn.nauka.gov.pl/works/534229 http://dx.doi.org/10.5281/zenodo.14881 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.10.2014. Revised 18.01.2015. Accepted: 25.01.2015. HOLY WATER CHANGES EEG AND HRV BECAUSE OF BOTH AUTOSUGGESTION AND HIS INFORMATION (GOD GRACE, WORLD MIND, COSMIC ENERGY etc) I L Popovych1, V Ye Babelyuk2, 3, A I Gozhenko3, W Zukow4, P G Zubov3, G I Dubkova2, T A Korolyshyn1, L F Nesterova1, L G Barylyak1 1JSC “Truskavets’kurort”, Truskavets’, Ukraine 2Clinical Sanatorium “Moldova”, Truskavets’, Ukraine 3Ukrainian scientific research Institute of Medicine of Transport Ministry of Public Health of Ukraine, Odessa 4Faculty Physical Culture, Health and Tourism, Kazimierz Wielki University, Bydgoszcz, Poland SUMMARY The aim: to identify the effects of Holy water on the parameters of HRV and EEG and clarify the role of autosuggestion and information. In 5 male volunteers performed 79 items HRV and EEG in the basal period and 25 tracks with 1,5 h after drinking 30 ml of water well, distilled, filtered, Holy (blind) and the well water indicates that it Holy (placebo ). Preliminary analysis revealed no significant differences between neurotropic effects of well, distilled and filtered waters, because for further analysis they were combined in a cluster "control waters". Found 48 parameters of HRV and EEG, in which a set of clusters "control waters", "Holy water" and "placebo" significantly different from each other and from the basal level. These parameters formed 9 patterns that demonstrate the stimulating or inhibitory neurotropic effect: 1) only placebo; 2) only Holy water; 3) placebo and Holy water as 3.1) opposite and 3.2) approximately equally. Conclusion: neurotropic effects Holy water is like autosuggestion and information (Divine) nature. Keywords: EEG, HRV, Holy water, placebo.